Algebraic time series forecasting and segmentation models - Lukoševičiūtė, Kristina; Palivonaitė, Rita (Lietuvos matematikos rinkinys, 2015)
An algebraic segmentation method based on algebraic predictor with internal smoothing is proposed. The concept of the rank of the sequence is proposed for the detection of a base fragment of the sequence. Numerical experiments with a real-world financial time series illustrate the segmentation method.